Effect of Clamp Type on Type II External Fixator Stiffness - Kraus, K. H.; Wotton, H. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
In order to investigate the effects of two clamp types on type II external fixator stiffness, models using wooden dowels were constructed and mechanically tested. Kirschner-Ehmer clamps were compared to Securos clamps in four-pin type II external fixator configurations. Increasing axial loads were applied and displacement at a gap in the centre of the model measured. Linear regression and comparison of the slope of the regression lines before yield, after yield, and throughout 700N assessed model performance. The resulting load displacement curves were linear. There was no difference in model stiffness before yield, but was greater with models constructed with Securos clamps after yield and overall. The mean relative stiffness of the models constructed with the Kirschner-Ehmer type clamps were 320 ± 53.8 Newtons/mm, and with models constructed with Securos type clamps were 425 ± 74.8 Newtons/mm. Utilizing Securos clamps resulted in significantly (p<0.05) greater frame stiffness that is attributable to higher load at yield and greater stiffness after yield. Increasing resistance to rotational moments at the clamp/connecting bar junction should result in less stress imparted to the bone/pin interface, decreasing strain and decreasing pin loosening.Axial stiffness in models of bilateral external fixators using Kirschner-Ehmer type clamps versus Securos clamps were compared. The stiffness of fixators constructed with Securos clamps was greater overall and at high loads due to a more secure fixation pin/connecting bar junction. Increased fixator stiffness would result in less stress at the bone/pin interface and may contribute to less pin loosening.
Keywords: External fixation; orthopaedics; biomechanics; alternatives